Accounting for the impact of conservation on human well-being. - Milner-Gulland, E; McGregor, J; Agarwala, M; Atkinson, G; Bevan, P; Clements, T; Daw, T; Homewood, K; Kumpel, N; Lewis, J; Mourato, S; Palmer Fry, B; et al. (2014)
Conservationists are increasingly engaging with the concept of human well-being to improve the design and evaluation of their interventions. Since the convening of the influential Sarkozy Commission in 2009, development researchers have been refining conceptualizations and frameworks to understand and measure human well-being and are starting to converge on a common understanding of how best to do this. In conservation, the term human well-being is in widespread use, but there is a need for guidance on operationalizing it to measure the impacts of conservation interventions on people. We present a framework for understanding human well-being, which could be particularly useful in conservation. The framework includes 3 conditions; meeting needs, pursuing goals, and experiencing a satisfactory quality of life. We outline some of the complexities involved in evaluating the well-being effects of conservation interventions, with the understanding that well-being varies between people and over time and with the priorities of the evaluator. Key challenges for research into the well-being impacts of conservation interventions include the need to build up a collection of case studies so as to draw out generalizable lessons; harness the potential of modern technology to support well-being research; and contextualize evaluations of conservation impacts on well-being spatially and temporally within the wider landscape of social change. Pathways through the smog of confusion around the term well-being exist, and existing frameworks such as the Well-being in Developing Countries approach can help conservationists negotiate the challenges of operationalizing the concept. Conservationists have the opportunity to benefit from the recent flurry of research in the development field so as to carry out more nuanced and locally relevant evaluations of the effects of their interventions on human well-being.